2011
DOI: 10.1371/journal.pone.0022507
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility and Biodegradation Studies of Subconjunctival Implants in Rabbit Eyes

Abstract: Sustained ocular drug delivery is difficult to achieve. Most drugs have poor penetration due to the multiple physiological barriers of the eye and are rapidly cleared if applied topically. Biodegradable subconjunctival implants with controlled drug release may circumvent these two problems. In our study, two microfilms (poly [d,l-lactide-co-glycolide] PLGA and poly[d,l-lactide-co-caprolactone] PLC were developed and evaluated for their degradation behavior in vitro and in vivo. We also evaluated the biocompati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 34 publications
3
37
0
Order By: Relevance
“…30 We also found that PA-loaded microfilm group had significantly less collagen encapsulation at 2 weeks, and less CD11c infiltration around the microfilms at 2 and 4 weeks in comparison with the blank microfilm group. It is well known that corticosteroids possess antifibrotic and anti-inflammatory actions.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…30 We also found that PA-loaded microfilm group had significantly less collagen encapsulation at 2 weeks, and less CD11c infiltration around the microfilms at 2 and 4 weeks in comparison with the blank microfilm group. It is well known that corticosteroids possess antifibrotic and anti-inflammatory actions.…”
Section: Discussionsupporting
confidence: 58%
“…In the surface erosion mode, also called heterogeneous degradation mode, there is a continuous decrease in volume or size as polymers degrade at the surface first, followed by dissolution of the surface layer. 30 In our study, the microfilms exhibited bulk degradation because the M w and M n decreased gradually throughout the study period, but no changes in the microfilm dimension or thickness (as seen in the histologic study) were observed during the initial 4 weeks. Furthermore, we also have examined the effect of PA loading onto microfilms, and we noted that blank and PA-loaded microfilms demonstrated quite similar degradation profiles ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 39%
See 1 more Smart Citation
“…16 The microspheres possessed a spherical shape, smooth surface, and diameter of 40-100 μm, with an in vitro release profile of more than 60 days, as analyzed in the previous studies. 6,15 PLGA-and/or PLA-sustained drug release systems applied in the eye have shown prolonged release of drugs 21,22 and have facilitated effective treatments for chronic ocular disorders such as proliferative vitreoretinopathy, retinal diseases, glaucoma, and neovascularization. The present researchers' previous studies have revealed that a single intravitreal injection of EPO-dextran PLGA/PLA microspheres could significantly protect retinas damaged from optic nerve crush in rats.…”
Section: Safety Evaluation Of Plga/pla Microspheres Through Intravitrmentioning
confidence: 99%
“…These characteristics allow PLC to have a slower hydrolysis rate, and therefore achieve a longer release. 28 Moreover, PLC copolymers are softer and more elastic, as it has a lower glass transition temperature than PLGA. 29 A softer material can minimize the surgical trauma during the implantation procedure as well as the risk of erosion or extrusion of the implant following the insertion.…”
Section: Discussionmentioning
confidence: 99%